Budgeting and Financial Planning in the Management Accounting System of Non-State Higher Education Institutions: Problems and Solutions - Xojiboyev Muxiddin Shodimuxamedovich (Research Parks Publishers, 2026)
This study investigates weaknesses in the current budgeting practices of non-state higher education institutions, including over-reliance on a single revenue source, a disconnect between financial planning and management accounting, and the absence of a responsibility centre framework. An integrated budgeting model grounded in responsibility centre principles with real-time variance tracking across all units is proposed.